Análisis comparativo de programas infantiles en medios públicos y comunitarios desde la perspectiva de la interculturalidad - Candelejo Alcarraz, Karen Ivonne (2018)
The purpose of the researching was to establish differences and similarities of children's content between public and community media, through a study case of intercultural programs "Wawakuna, and “sueños de los libros”. This is take into count to children and the aim is to examine the strategies that each uses to capture the importance of multiculturalism in its contents. In this sense, this project aims to study an comparative analysis of children's programs of public and community media in terms of multiculturalism from Educa TV studio and TV Micc in order to identify each communication used elements by production of their content.